Debate with the Visitors from the FRD (Czech Journal of International Relations, 1966)
On September 30, a three-member delegation of the now world-famous West German free organization was received at the Institute for International Politics and Economics in Prague, the Campaign for Disarmament, which arose from the Easter peace march against atomic weapons ("Atomwaffengegner"). This Campaign for Disarmament, uniting individual and entire organizations of the most diverse world opinion and political orientation (from pacifists, distinguished priests, religious, artists and other intellectuals and to individual trade unionists, even to the entire union and to student, trade union and socialist youth), it became unusually popular in the NSR during the six years of its existence around 135,000 of them in 1966. If we consider that usually only very active and determined people take part in strenuous and sometimes risky marches, we can conclude that the influence of the Campaign for Disarmament is many times greater, and thus not insignificant.